Overburden movement law in strip filling mining of upward mining faces - Lingjin Huang; Weiming Guan; Yu Guan; Hongchao Zhao; Zhiyi Zhang; Yingyuan Wen (Scientific Reports)
Abstract Strip filling mining significantly improves coal recovery rates and fosters sustainable development in the coal industry. To investigate the overburden movement patterns of strip filling mining, a mine in Tuokexun was selected as the study site. The stability of the composite structure in upward mining faces, as well as the stress distribution and fracture characteristics of the overburden at different stages of strip filling mining, were analyzed using theoretical methods, numerical simulations, and similarity experiments. The results show that, under the synergistic effect of coal pillars and filling material, a stable support structure can be achieved with an isolation coal pillar width of 15 m and a filling body width of 150 m. During the filling mining stage, the overburden damage range exhibits an upward-sloping trapezoidal distribution, with the lower section experiencing greater damage than the upper section, though the overall integrity remains intact, significantly reducing the risk of impact hazards. During the caving mining stage, the initial breaking spans of the immediate roof and main roof are 40 m and 80 m, respectively, with periodic breaking spans of 20 m, compared to traditional horizontal mining, the insufficient collapse of the lower goaf side requires focused protection. As the mining face advances, overburden displacement stabilizes, and stress concentration remains low without any significant stress mutations, contributing to the stability and safety of underground operations.